2016
DOI: 10.2147/imcrj.s107089
|View full text |Cite
|
Sign up to set email alerts
|

A case report of Epstein–Barr virus-associated retinal vasculitis: successful treatment using only acyclovir therapy

Abstract: The purpose of this study was to describe a presumed case of Epstein–Barr virus (EBV)-associated retinal vasculitis in a 42-year-old female with sudden unilateral vision loss and successful treatment with acyclovir therapy. Diagnostic vitreous biopsy of the right eye was performed to test for EBV and other known infectious causes of retinitis and evaluate vitreous cells and serological testing. Vitreous polymerase chain reaction viral DNA testing result was positive for EBV but negative for herpes simplex viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…An adequate number of vasculitis reports caused by EBV infection are identified in the literature [46][47][48][49][50][51]. It is interesting that some of these cases represent localized forms of vasculitis affecting only a single organ.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate number of vasculitis reports caused by EBV infection are identified in the literature [46][47][48][49][50][51]. It is interesting that some of these cases represent localized forms of vasculitis affecting only a single organ.…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified using PCR from the ocular fluids of eyes with anterior uveitis, vitritis, vasculitis and retinitis, and in 70% of normal cadaveric eyes . Reports have also identified its presence in eyes with ARN, mostly concomitantly with HSV or VZV, though there have also been cases where it was the only identified pathogen . Schaal et al demonstrated EBV DNA in the retinal cells of a patient with ARN, supporting its role in disease rather than as an indicator of lymphocyte migration.…”
Section: Epstein‐barr Virus Retinitismentioning
confidence: 99%
“…Treatment is based on a similar protocol to other causes of ARN, and reports have suggested a good response to the use of systemic and intravitreal aciclovir (Table ) …”
Section: Epstein‐barr Virus Retinitismentioning
confidence: 99%
See 2 more Smart Citations